Insecticide Treated Bed Net Usage Pattern in Ashaiman Municipality Accra - Oppong, O. (University of Ghana, 2014)
Malaria is the leading cause of morbidity and mortality in sub Saharan Africa. According to the Ghana’s Ministry of Health, malaria is estimated to cause the loss of about 10.6% of Disability Adjusted Life Years and estimated to cost about 6% of Gross Domestic Product annually. In the wake of drug resistance by the malaria parasites, Insecticide Treated Nets is seen as the most effective tool in controlling and eliminating malaria. Due to this, large scale of the Insecticide Treated Nets have been produced and freely distributed. However, studies have revealed that owning a bed net does not necessarily imply usage. There are other factors which influence the use of the ITNs. This study therefore explores factors that are associated with the use Insecticide Net usage pattern among residents in Ashaiman. The study employed both quantitative and qualitative research methods. Households with children less than five were interviewed using the snowballing sampling technique and personnel from the Ashaiman Municipal Health Directorate were interviewed. Although the primary use of the ITNs is for the protection of children under five because of their susceptibility to the malaria parasite, evidence from the data collected from the field shows that factors such as house structure and sleeping arrangements influence the use of the ITNs hence, defeating the purpose of the free distribution of the bed net in the area. The perceived benefit of the ITNs is not a guarantee in the usage of it. Results from the study also indicate that, people’s health seeking behavior does not always have biomedical explanations as some of the respondents attribute the susceptibility of children to the malaria parasite to their blood not being thick enough to withstand the mosquitoes. Implication of this study is that, free distribution of ITNs alone is not a guarantee to ensure the use of the bed nets but other factors such as the house structures and sleeping arrangements can also influence the use of the ITNs. Future antimalarial campaign should take into consideration the environmental as well as the housing aspect of the intervention program.
Thesis (MPhil) - University of Ghana, 2014
Keywords: Insecticide; Treated Net; Malaria; Malaria Parasite; Biomedical Explaination; Bed Net Usage Pattern